Comparative Study of Educational Achievement of Students of Funded and Self-Funded Secondary Schools of Mathura District - Singh, Rajesh Kumar (International Journal of Psychosocial Rehabilitation, 2020)
After careful editing, systematic classification and systematic correct tabulation of the arrangements, it is necessary that they are presented as achievements of the work so that the research leads to completion as well as in the context of the research work. It also seems necessary to describe the limitations that the researcher has realized. For the research work presented, the researcher has selected 100 students from funded secondary schools and 140 students from self-funded secondary schools. Analysis technique has been used in the presented research. Analysis technique has the name of statistical calculation methods under which compilation, organization, explanation of statistical data is explained.